My quest for negotiating meaning. Reflections on my dilemmas about practices of English language teaching in public school context in Turkey: An autoethnography - Öztürk, Huriye Arzu (Technium Social Sciences Journal, 2020)
The autoethnographic study aims to explore the teacher researcher’s dilemmas about the practices of English language teaching in the public school context in Turkey and the reasons behind them. Narratives were used to depict the experiences which led to the dilemmas; the researcher’s journey of learning, lived experiences and interactions in the community of practice. The narratives, which portrayed the emergence of dilemmas, were analysed through reflections on them. The reflections were also supported by the other mixed methods studies, theoretical and regulatory documents. The results demonstrate that the dilemmas arise from the gap between the theory and practices of English language teaching in the public school context in Turkey. The study is situated in the interpretivist paradigm of research and holistic-content analysis was used as a technique of narrative analysis. Vygotsky’s sociocultural theory of learning, Wenger’s community of practice, Dewey’s reflective practice, and Miller’s teacher identity concepts establish the theoretical framework of the study.